From Social Funds to Local Governance and Social Inclusion Programs : A Prospective Review from the ECA Region - Serrano-Berthet, Rodrigo (World Bank, Washington, DC, 2017)
The role and relevance of Social Funds/Community-Driven Development (SF/CDD) have been highly debated in the international development community. This debate is particularly relevant in the Europe andCentral Asia (ECA) region. Since the first social fund was created in 1993 in Albania, governments and donors have actively supported Social Funds in the Region as instrumentsto deal with a range of issues, from inadequate access to services, to local infrastructure provision, to social exclusion. The circumstances under which most Social Funds were created have changed significantly. The main objective of this report is to provide guidance toECA management and client governments on two questions: (i) Is the social fund instrument still relevant in the ECA region? Under what conditions? (ii) What are the future implications in terms ofcontinuation, transformation, and exit options under different country scenarios? The study gathered information from a universe of 16 SFs. Main data sources included bank documents; literature review; a questionnaire of social funds; short field trips to several countries (Georgia, Bosnia and Herzegovina, Romania, Turkey, Ukraine); and interviews with Task Team Leaders (TTLs).